To Sing the New Song… About the Art of Aggiornamento - Michaela Christine Hastetter (Polonia Sacra)
The postmodern comprehension of aggiornamento, which continues the tradition in a certain artistic freedom from the origin, is different from the well-balanced aggiornamento understanding of the Council Fathers. They intend to liberate the Christian from solidification as well as overgrowth and to focus on the essential of the Christian belief, namely Jesus Christ. In the recent time there has been additionally a historicizing tendency of aggiornamento, which looks back again at the historical performance practice and belongs to the field of it. Referring to statements of important Council fathers, aggiornamento is developed as a process with several aspects for the pastoral practice, which also includes an existential level.